(untitled) (Research, Society and Development, 2021)
Diabetes is a chronic non-communicable disease that requires continuous care, with multidisciplinary strategies, for risk reduction and glycemic control. The objective of the present work was to report the educational actions, the impact and the results of the “Projeto de Extensão Amigo do Diabético (PEAD): estratégias multidisciplinares de educação em saúde buscando melhorias na qualidade de vida do paciente diabético”. This project carries out consultations and health education actions, in Belém do Pará, for socioeconomically vulnerable patients and, in large part, coming from the interior of the state and from islands located around the capital of Pará. During its execution, the project collaborated with the Non-Governmental Organization Casa do Diabético in the medical assistance, education and health promotion of its users. It is important to highlight the relevance of university extension in the professional training of the students involved, who, in addition to establishing and maintaining university-community contact, also seeks to fill gaps in training and health care for patients with chronic non-communicable diseases, especially those in socioeconomic vulnerability. The elaboration of teaching materials, dissemination on social media and the realization of courses / workshops contributed to increase the autonomy of the patient and his health literacy, in addition to providing the necessary conditions for him to become an information multiplier agent in his social environment and self-managed their health condition.